2003
DOI: 10.1074/jbc.m210202200
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2, via Its BH4 Domain, Blocks Apoptotic Signaling Mediated by Mitochondrial Ras

Abstract: Bcl-2 protects cells against Ras-mediated apoptosis; this protection coincides with its binding to Ras. However, the protection mechanism has remained enigmatic. Here, we demonstrate that, upon apoptotic stimulation, newly synthesized Bcl-2 redistributes to mitochondria, interacts there with activated Ras, and blocks Ras-mediated apoptotic signaling. We also show, by employing bcl-2 mutants, that the BH4 domain of Bcl-2 binds to Ras and regulates its anti-apoptotic activity. Experiments with a C-terminal-trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 58 publications
2
42
0
1
Order By: Relevance
“…4,5,[29][30][31][32][33] Moreover, some bcl-2 protein interactors, such as the bcl-2 mitochondrial chaperone FKBP38, the orphan nuclear receptor Nur77 and the molecular chaperone HSP90, have been demonstrated to be involved in oxygen-dependent and -independent regulation of the HIF-1a protein. [33][34][35] Even if we recently demonstrated that bcl-2 protein under hypoxic conditions interacts with both HIF-1a and HSP90 proteins contributing to the enhancement of HIF-1a protein stability, 21 we cannot exclude that also other bcl-2 interactors can be involved in bcl-2-induced HIF-1a/VEGF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[29][30][31][32][33] Moreover, some bcl-2 protein interactors, such as the bcl-2 mitochondrial chaperone FKBP38, the orphan nuclear receptor Nur77 and the molecular chaperone HSP90, have been demonstrated to be involved in oxygen-dependent and -independent regulation of the HIF-1a protein. [33][34][35] Even if we recently demonstrated that bcl-2 protein under hypoxic conditions interacts with both HIF-1a and HSP90 proteins contributing to the enhancement of HIF-1a protein stability, 21 we cannot exclude that also other bcl-2 interactors can be involved in bcl-2-induced HIF-1a/VEGF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…35 These domains have been described to be involved in Bcl-2, Bax, and other interacting proteins' hetero-and homodimerizations that consequently modulate apoptosis. 35,36 For instance, the conserved N-terminal BH4 domain of Bcl-2 homologues is essential for inhibition of apoptosis. 37 Our studies indicate that deletion of BH4 domain led to a loss of binding of Bcl-2 with Rap1b, whereas it was unaffected by deletion of other domains, suggesting that the binding is specific ( Figure 5); and conceivably Rap1b stabilizes the antiapoptotic effect of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…The total protein concentrations in the cell lysates were normalised and adjusted to 0.4 M NaCl, 0.5% deoxycholate and 0.05% SDS for immunoblotting (Denis et al, 2003). The samples were separated on a 10% SDS -polyacrylamide gel electrophoresis gel and subsequently transferred to a nitrocellulose membrane.…”
Section: Immunoblotmentioning
confidence: 99%